2000
DOI: 10.1292/jvms.62.693
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Taurine in Rat Milk on the Growth of Offspring.

Abstract: ABSTRACT. The physiological significance of taurine in milk in the growth of rat pups was investigated. Our results confirmed that taurine was at an exceptionally high concentration in rat milk during the lactational period, especially for the first few days after birth. Pups taking no milk from natural dams but from foster mothers at an advanced lactational period showed a slower growth rate. Intraperitoneal administration of taurine to the foster mothers in the first five days restored this growth retardatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
17
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 29 publications
7
17
1
Order By: Relevance
“…Further study should be done to clarify this hypothesis. As pointed out in the introduction, tissue taurine depletion could induce physiological dysfunctions such as growth retardation (Sturman, 1993;Hu et al, 2000). In the present study, no significant negative effects were observed in growth parameters such as feed consumption, body weight gain, feed efficiency, MPS weight and whole brain weight (Table 1).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Further study should be done to clarify this hypothesis. As pointed out in the introduction, tissue taurine depletion could induce physiological dysfunctions such as growth retardation (Sturman, 1993;Hu et al, 2000). In the present study, no significant negative effects were observed in growth parameters such as feed consumption, body weight gain, feed efficiency, MPS weight and whole brain weight (Table 1).…”
Section: Discussionsupporting
confidence: 55%
“…β-Ala levels of brain, MPS and plasma were dose-dependently increased while their taurine levels were decreased in a dose-dependent manner. Taurine depletion was commonly observed following β-Ala treatment because β-Ala competes with taurine for uptake (Hu et al, 2000;Tomonaga et al, 2005bTomonaga et al, , 2006. The supplemental β-Ala in the present study successfully competed with taurine.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The hepatic taurine pool appears to increase just before parturition and rapidly decrease after the first few days of lactation when high levels of taurine are secreted into the milk [15]. However, the data in our previous study indicated that taurine concentrations in milk always highly exceeded those in dams' peripheral circulation, and administration of β-alanine, a transport antagonist of taurine, to lactating dams did not decrease taurine concentrations in the milk [5]. These observations make us hypothesize that taurine can be synthesized by the mammary gland, and that taurine synthesized in the mammary gland may be another important source of taurine in the milk.…”
contrasting
confidence: 56%
“…We have also recently shown that high concentrations of taurine, especially at the beginning of lactation, is mandatory for normal body growth of rat pups presumably by maintaining insulin-like growth factor-I (IGF-I) levels in the blood [5]. Taurine in milk is thought to be derived from the liver, because the milk taurine level was positively correlated with hepatic taurine concentration during a lactational period [15].…”
mentioning
confidence: 99%